2020
DOI: 10.1002/fsh.10491
|View full text |Cite
|
Sign up to set email alerts
|

A Fishery after the Decline: The Susquehanna River Smallmouth Bass Story

Abstract: The Smallmouth Bass Micropterus dolomieu fishery in the Susquehanna River basin, Pennsylvania, is one of the most socioeconomically important fisheries in the region and has recently undergone considerable changes. These changes started in 2005, when disease was documented in young-of-the-year (age-0) Smallmouth Bass. Shortly thereafter, declines in abundance of both juveniles and adults were observed. These declines in abundance coincided with disease infections in age-0, intersex in adults, and concerns rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Under climate change, availability of favorable thermal conditions will continue to increase elsewhere across the western United States (Isaak et al 2017b), with specific examples presented here in the Chehalis River but also in the Columbia River basin (Rubenson and Olden 2020) and a tributary of the North Platte River (Kirk et al 2022). This contrasts with habitat within the native range of Smallmouth Bass, where thermal conditions are expected to exceed favorable thresholds under climate change (Birdsong et al 2015;Middaugh and Magoulick 2018;Schall et al 2020). Nevertheless, in both scenarios, restoration actions related to stream temperature cooling are critical for managing Smallmouth Bass populations (Whitledge et al 2006).…”
Section: Modelmentioning
confidence: 99%
“…Under climate change, availability of favorable thermal conditions will continue to increase elsewhere across the western United States (Isaak et al 2017b), with specific examples presented here in the Chehalis River but also in the Columbia River basin (Rubenson and Olden 2020) and a tributary of the North Platte River (Kirk et al 2022). This contrasts with habitat within the native range of Smallmouth Bass, where thermal conditions are expected to exceed favorable thresholds under climate change (Birdsong et al 2015;Middaugh and Magoulick 2018;Schall et al 2020). Nevertheless, in both scenarios, restoration actions related to stream temperature cooling are critical for managing Smallmouth Bass populations (Whitledge et al 2006).…”
Section: Modelmentioning
confidence: 99%
“…Laboratory experiments by Boonthai et al ( 2018 ) found that LMBV isolates from Susquehanna River drainage populations of Smallmouth Bass were capable of causing mortality of age 0 Smallmouth Bass and this was exacerbated by coinfection of other pathogens and environmental attributes (i.e., temperature > 23°C). Additionally, population declines occurred in portions of the Susquehanna River basin because of limited recruitment that resulted from repeated mortality events of age 0 Smallmouth Bass (Li et al 2018b ;Schall et al 2020 ). It was clear that this was not a simple single factor cause-effect scenario.…”
Section: Fisheriesmentioning
confidence: 99%
“…Research fi ndings have been directly incorporated into fi shing regulations for Smallmouth Bass (e.g., considering among river movement of fi sh in management implications), led to updated biosecurity protocols for researchers and fi eld crews, and used to refi ne monitoring assessments for biota (e.g., tracking and evaluation of fi sh disease characteristics and inclusion of wild fi sh health surveys) and chemical contaminants in Pennsylvania. Fortunately for Smallmouth Bass in the Susquehanna River basin, populations are recovering (i.e., catch rates have increased), disease prevalence decreased, and recruitment improved, and because of our collaborative research we not only have a better understanding of risk factors for disease, but are more prepared for future challenges that may emerge (Li et al 2018a ;Schall et al 2020 ).…”
Section: Future Considerationsmentioning
confidence: 99%
“…Research findings have been directly incorporated into fishing regulations for Smallmouth Bass (e.g., considering among river movement of fish in management implications), led to updated biosecurity protocols for researchers and field crews, and used to refine monitoring assessments for biota (e.g., tracking and evaluation of fish disease characteristics and inclusion of wild fish health surveys) and chemical contaminants in Pennsylvania. Fortunately for Smallmouth Bass in the Susquehanna River basin, populations are recovering (i.e., catch rates have increased), disease prevalence decreased, and recruitment improved, and because of our collaborative research we not only have a better understanding of risk factors for disease, but are more prepared for future challenges that may emerge (Li et al 2018a; Schall et al 2020).…”
Section: Future Considerationsmentioning
confidence: 99%
“…Laboratory experiments by Boonthai et al (2018) found that LMBV isolates from Susquehanna River drainage populations of Smallmouth Bass were capable of causing mortality of age 0 Smallmouth Bass and this was exacerbated by coinfection of other pathogens and environmental attributes (i.e., temperature > 23°C). Additionally, population declines occurred in portions of the Susquehanna River basin because of limited recruitment that resulted from repeated mortality events of age 0 Smallmouth Bass (Li et al 2018b; Schall et al 2020). It was clear that this was not a simple single factor cause–effect scenario.…”
Section: Introductionmentioning
confidence: 99%